Beautiful closed form!

Calculus Level 5

n = 0 ( 2 ( 2 n + 1 ) ( ( 2 n + 2 ) + 3 ( 3 n + 1 ) ( 3 n + 2 ) ( 3 n + 3 ) + 4 ( 4 n + 1 ) ( 4 n + 2 ) ( 4 n + 3 ) ( 4 n + 4 ) ) ( 1 ) n ( n + 1 ) \sum_{n=0}^{\infty}\left(\frac{2}{(2n+1)((2n+2)} +\frac{3}{(3n+1)(3n+2)(3n+3)} +\frac{4}{(4n+1)(4n+2)(4n+3)(4n+4)}\right)(-1)^n(n+1) If the closed form the above sum can be expressed as a b log a + π c ( d + a ) \dfrac{a}{b}\log a + \dfrac{\pi}{c}\,(d+ \sqrt a) , where a a and b b are primes, Find the value of a + b + c + d a+b+c+d .


Source: Romanian Mathematical Mazagine

This problem was proposed by Sir. Srinivasa Raghava, India in RMM, where proposer supposed to show the closed form .


For more problems you may wish to visit RMM .


The answer is 14.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Naren Bhandari
Oct 30, 2018

My approach

Note that given summation can be further simplified to n = 0 ( ( 1 ) n ( 2 n + 1 ) + ( 1 ) n ( 3 m + 1 ) ( 3 m + 2 ) + ( 1 ) n ( 4 m + 1 ) ( 4 m + 2 ) ( 4 m + 3 ) ) \sum_{n=0}^{\infty} \left(\dfrac{(-1)^n}{(2n+1)} + \dfrac{(-1)^n}{(3m+1)(3m+2)} +\dfrac{(-1)^n}{(4m+1)(4m+2)(4m+3)}\right) Now let us make individual evaluation of the each sum. Φ 1 = n = 0 ( 1 ) n ( 2 n + 1 ) = 0 1 1 1 + x 2 d x = π 4 \Phi_{1} =\sum_{n=0}^{\infty} \dfrac{(-1)^n}{(2n+1)} =\int_{0}^{1} \dfrac{1}{1+x^2}\,dx =\dfrac{\pi}{4} Similarly, Φ 2 = n = 0 ( 1 ) n ( 3 m + 1 ) ( 3 m + 2 ) = n = 0 ( ( 1 ) n ( 3 m + 1 ) ( 1 ) n ( 3 m + 2 ) ) = n = 0 ( ( 1 ) n n + 1 1 3 ( 1 ) n n + 1 ) = 2 3 n = 0 ( 1 ) n n + 1 = 2 3 0 1 1 1 + x d x = 2 3 log 2 \begin{aligned} \Phi_{2} & = \sum_ {n=0}^{\infty} \dfrac{(-1)^n}{(3m+1)(3m+2)} \\&= \sum_{n=0}^{\infty}\left(\dfrac{(-1)^n}{(3m+1)} -\dfrac{(-1)^n}{(3m+2)}\right)\\& =\sum_{n=0}^{\infty}\left(\dfrac{(-1)^n}{n+1}-\dfrac{1}{3}\dfrac{(-1)^n}{n+1}\right)= \dfrac{2}{3}\sum_{n=0}^{\infty} \dfrac{(-1)^n}{n+1} = \dfrac{2}{3}\int_{0}^{1}\dfrac{1}{1+x}\,dx = \dfrac{2}{3}\log2 \end{aligned} Finally, Φ 3 = n = 0 ( 1 ) n ( 4 n + 1 ) ( 4 n + 2 ) ( 4 n + 3 ) \Phi_{3} = \sum_{n=0}^{\infty} \dfrac{(-1)^n}{(4n+1)(4n+2)(4n+3)} Since ( 1 ) n ( 4 n + 1 ) ( 4 n + 2 ) ( 4 n + 3 ) = ( 1 ) n 2 ( 1 4 n + 1 2 4 n + 2 + 1 4 n + 3 ) \dfrac{(-1)^n}{(4n+1)(4n+2)(4n+3)} = \dfrac{(-1)^n}{2}\left(\dfrac{1}{4n+1} -\dfrac{2}{4n+2} +\dfrac{1}{4n+3}\right) Now note that above decompose portion can be further written as Φ 3 = 1 2 n = 0 0 1 ( x 4 n + x 4 n + 2 ) d x 1 2 n = 0 ( 1 ) n 2 n + 1 = 1 2 0 1 ( 1 1 + x 4 + x 2 1 + x 4 ) d x 1 2 ( n = 0 ( 1 ) n 2 n + 1 ) = 1 2 0 1 ( 1 + x 2 1 + x 4 1 ( 1 + x 2 ) ) d x = I 2 π 2 4 = π 4 2 π 8 \begin{aligned} \Phi_3& = \dfrac{1}{2}\sum_{n=0}^{\infty} \int_{0}^{1} \left( x^{4n} + x^{4n+2}\right)\,dx-\dfrac{1}{2}\sum_{n=0}^{\infty} \dfrac{(-1)^n}{2n+1}\\& =\dfrac{1}{2}\int_{0}^{1}\left(\dfrac{1}{1+x^4}+\dfrac{x^2}{1+x^4}\right)\,dx-\dfrac{1}{2}\left(\sum_{n=0}^{\infty}\dfrac{(-1)^n}{2n+1}\right) \\& = \dfrac{1}{2}\int_{0}^{1}\left(\dfrac{1+x^2}{1+x^4}-\dfrac{1}{(1+x^2)}\right)\,dx\\& = \dfrac{I}{2}-\dfrac{\pi}{2\cdot 4} = \dfrac{\pi}{4\sqrt 2} -\dfrac{\pi}{8}\end{aligned} Thus we have then Φ 1 + Φ 2 + Φ 3 = 2 3 log 2 + π 8 ( 1 + 2 ) \Phi_1 +\Phi_2 +\Phi_3 = \dfrac{2}{3}\log2 +\dfrac{\pi}{8}(1+\sqrt 2) Making a + b + c + d = 14 a+b+c+d=14 .


Note I = 1 + x 2 1 + x 4 d x = 1 2 0 1 2 ( x 2 + 1 ) x 4 + 1 d x I = \int\dfrac{1+x^2}{1+x^4} \,dx=\dfrac{1}{2}\int_{0}^{1}\dfrac{2(x^2+1)}{x^4+1}\,dx since x 4 + 1 = ( x 2 + 2 x + 1 ) ( x 2 2 x + 1 ) x^4+1= (x^2+\sqrt 2 x+1)(x^2-\sqrt 2 x+1) Hence I = 1 2 ( 1 x 2 + 2 x + 1 + 1 x 2 2 x + 1 ) d x = 2 2 ( tan 1 ( x 2 + 1 ) + tan 1 ( x 2 1 ) ) + C \begin{aligned} I & = \int\dfrac{1}{2}\left(\dfrac{1}{x^2+\sqrt 2x+1} +\dfrac{1}{x^2-\sqrt 2x +1}\right)\,dx\\&= \dfrac{\sqrt2 }{2}\left(\tan ^{-1} (x\sqrt 2+1)+\tan ^{-1}(x\sqrt 2 -1)\right)+C \end{aligned} setting the limit gives = 1 2 tan 1 ( 2 x 1 x 2 ) = π 2 2 = \dfrac{1}{\sqrt 2} \tan ^{-1}\left(\dfrac{\sqrt 2 x}{1- x^2}\right) =\dfrac{\pi}{2\sqrt 2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...